Digital channels and technologies for commercial diplomacy: conceptualisation and future research propositions. (2015) - Sevin, Efe; Dinnie, Keith
In this article, we provide a conceptual framework for the practice and study of commercial diplomacy in the light of two developments in the field of diplomacy. The first development in the field is related to the relative popularity of two new terms in diplomatic practice: public diplomacy and nation branding. The second development is the role of information and communication technologies (ICTs). Our main objective is to clear the conceptual ambiguity by demonstrating the role of commercial diplomacy in the larger framework of diplomatic practices and the interdependence of commercial diplomacy, nation branding, and public diplomacy specifically in the age of digital communications. With our model, we hope to bridge the gaps between different practices, concepts, and fields of studies.